Ovalbumin’s potential as a wound-healing medicament in tooth extraction socket by induction of cell proliferation through the ERK2 pathway in silico - Sri Nabawiyati Nurul Makiyah; Sartika Puspita (Dental Journal, 2023)
Background: The trend of studies on dental medicaments is increasing rapidly. Antibacterial or anti-inflammatory activity is most frequently studied. Ovalbumin is one of the proteins whose benefits have been studied, but these benefits are still limited because of ovalbumin’s potential for proliferative bioactivity. Purpose: The aim of this study is to examine ovalbumin’s potential as a woundhealing medicament through molecular docking analysis on a protein related to the extracellular signal-regulated kinases/mitogenactivated protein kinase (ERK/MAPK) signaling pathway. Methods: Ovalbumin was hydrolyzed through BIOPEP-UWM (The BIOPEPUWM™ database of bioactive peptides). Protein target and interaction were predicted using Similarity Ensemble Approach target prediction webserver, SuperPred webserver, STRING webserver, and Cytoscape version 3.9.1. Selected fragments were docked using Autodock Vina in PyRx 0.8 with Tukey’s multiple comparison test and Biovia Discovery Studio version 19.1.0.18287 for visualization. Results: This study found that ovalbumin has the potential to positively regulate cell proliferation, angiogenesis, and fibroblast growth factor production. Six of the 131 fragments of ovalbumin could interact with 73 proteins, and the 20 proteins with the highest probability and score of betweenness centrality showed potential for bioactivity. Five fragments and povidone-iodine interacted inside the Adenosine triphosphate (ATP) phosphorylation site of ERK2, whereas fragment 1 (F1) and glycerin interacted outside the site. F1 could decrease the binding energy required for adenosine 5′-[,-methylene]triphosphate or an ATP-analogue chemical compound to interact with ERK2 compared to the control, with a score that was not significant. Conclusion: Ovalbumin has the potential to induce cell proliferation by affecting ERK2-ligand interactions.